Hubungan Spiritual Well-Being Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisis - Yola Yolanda (CV. ITTC INDONESIA, 2026)
Chronic kidney disease (CKD) is a disease that affects many people around the world. One of the consequences of CKD is a disruption in the patient's quality of life. The quality of life of CKD patients can be influenced by spiritual well-being. High spiritual well-being in CKD patients can help them feel closer to God and find meaning and purpose in their lives. This study aims to determine the relationship between Spiritual Well-Being and quality of life in CKD patients undergoing hemodialysis. This study uses a quantitative approach with a cross-sectional study design. This study was conducted at Dr. Reksodiwiryo Hospital from May to June 2025. The study sample consisted of 75 CKD patients undergoing hemodialysis, selected using purposive sampling. Data collection was conducted using the SWBS questionnaire and the KDQOL 36 questionnaire through interviews. Data analysis was performed using univariate and bivariate analysis with a chi-square test p-value ≤0.05. The univariate results showed that 31 (41.3%) patients had moderate spiritual well-being. More than half (44 or 58.7%) had a good quality of life. The chi-square test yielded a p-value of 0.001. The results of this study indicate that there is a relationship between spiritual well-being and quality of life in CKD patients undergoing hemodialysis at Dr. Reksodiwiryo Hospital in Padang. It is hoped that hospital medical staff can provide support to CKD patients undergoing hemodialysis in the form of audiovisual therapy and spiritual education such as recitation of the Qur'an and dzikr.